2015
DOI: 10.1002/crat.201500085
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of flower‐like CdS prepared by a hydrothermal method with SDBS as surfactant

Abstract: In this article, flower-like CdS structures have been prepared by a hydrothermal method with SDBS as surfactant. The influences of different experimental conditions on the morphologies, UV-Vis and fluorescence properties of CdS have been investigated. The performances of CdS have been analyzed by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), ultraviolet-visible (UV-Vis) and room-temperature photoluminescence (PL). The XRD result indicates that the flower-like CdS structures are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The widening in the band gap can be attributed to the increased thiourea concentration, change in morphology and surface nanostructures. 42,43 It has been reported that an increase in thiourea concentration reduces the particle size and widens the band gap. 15 3.9 Photo electrochemical solar cell study Fig.…”
Section: Optical Absorption Studiesmentioning
confidence: 99%
“…The widening in the band gap can be attributed to the increased thiourea concentration, change in morphology and surface nanostructures. 42,43 It has been reported that an increase in thiourea concentration reduces the particle size and widens the band gap. 15 3.9 Photo electrochemical solar cell study Fig.…”
Section: Optical Absorption Studiesmentioning
confidence: 99%